Implementation of Religiously Content Dialectical Behavior Therapy (DBT) in Developing Academic Resilience - Ahmad Jawandi (Zien Journals, 2023)
Problems and difficulties in life are sunnatullah that must be faced by every human being. This is where it is important to build student academic resilience so that they always survive and are adaptive in facing every challenge and obstacle in their lives. This study aims to develop students' academic resilience or resilience through Dialectical Behavior Therapy (DBT) with religious content. The methodology in this research uses experiments with a population of Slamet Riyadi University students in Surakarta. The sample in this study was taken through a purposive sampling technique, namely students who have low academic resilience. The instrument for collecting quantitative data uses a resilience scale which is then analyzed to compare the pretest and posttest through the Wilcoxon test formula with the SPSS application. The conclusion of this study shows that Dialectical Behavior Therapy (DBT) with religious content is effective for increasing academic resilience as evidenced by the significance value of the experimental group different testresults of 0.005 < 0.05.
Keywords: Dialectical; Behavior; Resilience